Magnetic resonance imaging measurement of placental perfusion and oxygen saturation in early‐onset fetal growth restriction. (5th August 2020) - Aughwane, R; Mufti, N; Flouri, D; Maksym, K; Spencer, R; Sokolska, M; Kendall, G; Atkinson, D; Bainbridge, A; Deprest, J; Vercauteren, T; Ourselin, S; et al.
Abstract : Objective: We hypothesised that a multi‐compartment magnetic resonance imaging (MRI) technique that is sensitive to fetal blood oxygenation would identify changes in placental blood volume and fetal blood oxygenation in pregnancies complicated by early‐onset fetal growth restriction (FGR). Design: Case–control study. Setting: London, UK. Population: Women with uncomplicated pregnancies (estimated fetal weight [EFW] >10th centile for gestational age [GA] and normal maternal and fetal Doppler ultrasound, n = 12) or early‐onset FGR (EFW <3rd centile with or without abnormal Doppler ultrasound <32 weeks GA, n = 12) were studied. Methods: All women underwent MRI examination. Using a multi‐compartment MRI technique, we quantified fetal and maternal blood volume and feto‐placental blood oxygenation. Main outcome measures: Disease severity was stratified according to Doppler pulsatility index and the relationship to the MRI parameters was investigated, including the influence of GA at scan. Results: The FGR group (mean GA 27 +5 weeks, range 24 +2 to 33 +6 weeks) had a significantly lower EFW compared with the control group (mean GA 29 +1 weeks; −705 g, 95% CI −353 to −1057 g). MRI‐derived feto‐placental oxygen saturation was higher in controls compared with FGR (75 ± 9.6% versus 56 ± 16.2%, P = 0.02, 95% CI 7.8–30.3%). Feto‐placental oxygen saturation estimation correlated strongly with GA at scan in controls ( r = −0.83). Conclusion: Using a novel multimodal MRI protocol we demonstrated reduced feto‐placental blood oxygen saturation in pregnancies complicated by early‐onset FGR. The degree of abnormality correlated with disease severity defined by ultrasound Doppler findings. Gestational age‐dependent changes in oxygen saturation were also present in normal pregnancies. Tweetable abstract: MRI reveals differences in feto‐placental oxygen saturation between normal and FGR pregnancy that is associated with disease severity. Tweetable abstract: MRI reveals differences in feto‐placental oxygen saturation between normal and FGR pregnancy that is associated with disease severity.